Geriatric Patient Outcomes of Major Burn due to High-Voltage Electrical Injury: A Case Report - Vincent Anggriant; Ratna Rayeni Natasha Roosseno; Daniel Puguh Pramudyo; Yoseph Chandra (Intisari Sains Medis, 2022)
Introduction: Electrical burns are uncommon but result in high morbidity and mortality due to severe tissue damage. Geriatrics are vulnerable to aggressive burns because of skin atrophy, comorbidities, diminished host defence mechanisms and reduced mobility. A high-voltage electrical injury has complex complications, especially long-term complications. This study aimed to present the case of geriatric patient outcomes of major burn due to high-voltage electrical injury. Case Presentation: This is a case report of electrical burn injuries; a 70 years old man came to the emergency room approximately 1 hour after the incident, and a chief complaint was burning due to electrical shock. The patient had a history of electrical shock when fishing on the side of the river bank, where there is a high-voltage electrical central behind him. When he threw his fishing line, the fishing line caught on the exposed high-voltage transformer cable causing an electric shock. The examination showed that the patient was conscious of burns on the right chest to the abdomen and palm to the right hand, as well as on both soles of the feet. Another complaint was a pain in the wound due to electrical shock without a history of fainting, shortness of breath, chest pain, headache, and vomiting. The patient’s previous medical history showed uncontrolled hypertension. Conclusion: Our study demonstrates a rare geriatric patient discharged without complications due to a high-voltage injury. Strict multi-specialty management and rehabilitation are required to treat electrical injuries properly.